Psychological Distress, Anxiety, and Academic Self-Efficacy as Predictors of Study Satisfaction Among Peruvian University Students During the COVID-19 Pandemic - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Caycho-Rodriguez, Tomás; Lingán-Huamán, Susana K.; Ruiz Mamani, Percy G. (Frontiers in Psychology, 2022)
This research is aimed at assessing whether psychological distress, anxiety, and academic self-efficacy can help predict study satisfaction among Peruvian university students during the COVID-19 pandemic. This is a predictive and cross-sectional study involving 582 Peruvian university students, including 243 male and 339 female students between 16 and 41 years of age. For information collection purposes, the Brief Scale of Study Satisfaction (EBSE, for its Spanish acronym), the Generalized Anxiety Disorder Scale-2 (GAD-2), the Academic Self-Efficacy Scale (ASES), and the Kessler Psychological Distress Scale (K6) were used, while a Pearson correlation research and multiple linear regression analyses were conducted. Psychological distress, anxiety, academic self-efficacy, and study satisfaction have been found to be significantly correlated. Likewise, statistically significant differences were observed between men and women with regard to psychological distress, anxiety, and academic self-efficacy. In order to determine which variables can better predict study satisfaction, a multiple linear regression analysis was carried out, the results of which indicate that academic self-efficacy accounts for 18.4% of the total variance of the study satisfaction variable. In conclusion, academic self-efficacy predicts study satisfaction.